The Effect of Capital Intensity, Sales Growth, Inventory Intensity, and Profitability on Tax Aggressiveness (Empirical Study on Food, and Beverage Sub-Sector Manufacturing Companies Listed on the Indonesia Stock Exchange in 2020-2023) - Dio Janitra Rizanta; Emylia Yuniartie; Meita Rahmawati (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This research explores the influence of capital intensity, sales growth, inventory intensity, and profitability on tax aggressiveness in manufacturing companies within the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023. Tax aggressiveness is measured using the effective tax rate method. The population of this study consists of food and beverage sub-sector manufacturing firms listed on the IDX during the specified period. The sample was selected using a purposive sampling method, resulting in a total of 101 samples. The data were analyzed using multiple linear regression analysis with the assistance of SPSS 26 software. The results indicate that capital intensity, sales growth, and inventory intensity do not have a significant effect on tax aggressiveness. However, profitability has a significant influence on tax aggressiveness.